1982
DOI: 10.1258/002367782780908850
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion in inbred strain-2 weanling guineapigs

Abstract: SummaryThe incidence of malocclusion was recorded for 4 years. Malocclusion occurred only in animals less than 2 months old. The incidence was significantly reduced (P > 0.001) by breeding from animals without affected siblings: it is suggested that malocclusion in this colony has a genetic basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Diet may not be as important a factor in causing dental disease as often perceived. Rather, lack of occlusion, due to either acquired or hereditary factors, appears more plausible, and both effects of minerally imbalanced diets (Jekl and Redrobe, ) and genetic involvement (Rest et al., ) have been demonstrated in rodents. Therefore, we recommend that clinicians take into account these other reasons for dental disease, such as mineral imbalances (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet may not be as important a factor in causing dental disease as often perceived. Rather, lack of occlusion, due to either acquired or hereditary factors, appears more plausible, and both effects of minerally imbalanced diets (Jekl and Redrobe, ) and genetic involvement (Rest et al., ) have been demonstrated in rodents. Therefore, we recommend that clinicians take into account these other reasons for dental disease, such as mineral imbalances (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Again, this shifts the focus to other factors, in particular hereditary ones. Although detailed studies are lacking, Rest et al (1982) reported the occurrence of malocclusion, including photographic documentation of 'bridge formation' of the mandibular cheek teeth, in a colony of guinea pigs where the problem could be reduced when excluding relatives of affected animals from breeding.…”
Section: Experimental Set-upmentioning
confidence: 99%